Beacon-mediated exponential amplification reaction (BEAR) using a single enzyme and primer. Issue 72 (19th August 2019) - Newbigging, Ashley M.; Zhang, Hongquan; Le, X. Chris
Abstract : Beacon-mediated Exponential Amplification Reaction (BEAR ) enables isothermal, exponential signal amplification.BEAR uses only a single enzyme and a single primer. Abstract : Beacon-mediated Exponential Amplification Reaction (BEAR ) enables isothermal, exponential signal amplification.BEAR uses only a single enzyme and a single primer. Detection of 0.2 amol of a mitochondrial DNA with a point mutation in less than an hour demonstrates an application of theBEAR technique for nucleic acid research.